Synthesis and utility of new amine/nucleobase addition products of allenylphosphonates - Swamy, K. C. Kumara; Balaraman, Ekambaram; Kumar, N. Satish (Tetrahedron, 2006)
In the reaction of allenylphosphonates with amines/nucleobases, depending on the amine and the allenylphosphonate, either Z- or E-vinylphosphonate or allylphosphonate as a single isomer with a β-amino functionality was isolated. A simple route to phosphonates with a β-NH2 group is developed by direct reaction with ammonia. In reactions with adenine, three different modes of reaction, with one of them involving an unusual cyclisation, are observed. The utility of (enamino)allyl phosphonate products thus obtained in the synthesis of (enamino)-1,3-butadienes via Horner–Wadsworth–Emmons (HWE) reaction is also demonstrated.